ANALISIS PROSES MORFOLOGIS PADA CERPEN ULIAN KANGEN KARYA I NYOMAN AGUS SUDIPTA - Sari, Ni Wayan Nia Novita (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
The word formation is one of the important studies in the field of linguistics because each language has its own system and pattern for forming words through morphological processes. Morphology as a branch of microlinguistic studies focuses on analyzing morphemes, words, and the combinations formed in them, which are the basis for understanding the structure and process of word formation in a language. This research discusses the morphological process of Balinese words contained in the short story literary work entitled Ulian Kangen from the collection of short stories Ngrebutin Abu by I Nyoman Agus Sudipta. The analysis focuses on morphological patterns such as affixation, reduplication, and fusion by using the text of the Ulian Kangen short story as the main data source. This research belongs to the type of qualitative research, namely words or phrases in Balinese, which are analyzed descriptively to identify and explain word formation patterns in depth. The data was collected using the listening method and note-taking technique to document the data. The analysis stage is carried out by identifying, classifying, and analyzing word formation patterns based on morphological theory, then interpreting the characteristics of morphological processes in Balinese. Based on the results of the research, it was found that the short story Ulian Kangen contains various morphological processes in Balinese. The affixation process includes the use of prefixes {sa-}, {ma-}, {ka-}; suffixes {-a}, {-ang}, {-in}, {-né}; confixes; but there is no infix in this short story. The reduplication process consists of pure repeats rewords, pseudo repeats words, and phoneme change rewords. The composition process includes unequal compound words and compound words that have unique elements.